The silence of Adam becoming men of courage in a world of chaos - Crabb, Lawrence J.; Andrews, Al, 1954-; Hudson, Don, 1959- (Grand Rapids, MI Zondervan, 1995)
24cm
Keywords: Men (Christian theology).; Men -- psychology; Men -- religious life